Analysis of the Influence of Denison’s Organizational Culture Model on Employee Engagement and Organizational Effectiveness - Nila Cahya; M. Riza Firdaus (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to analyze the influence of Denison's organizational culture model on employee engagement and organizational effectiveness. The Denison model is used because it focuses on four key dimensions: engagement, consistency, adaptability, and mission, which allows for a more measurable and concrete evaluation of organizational culture. This study used a quantitative approach with a survey method through questionnaires distributed to employees. The data obtained were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationship between these variables. The results showed that organizational culture has a significant influence on employee engagement and organizational effectiveness. In addition, this study found that employee engagement has a significant influence on organizational effectiveness. The analysis of Denison's model of organizational culture shows that the dimensions interact and contribute to creating a work environment that supports employee engagement and increased organizational effectiveness. This research emphasizes the importance of an in-depth understanding of organizational culture in the context of MSMEs, thus providing new and relevant insights for developing organizational management theory and practice in the MSME sector.